(untitled) (Contemporary Mathematics, 2025)
This study introduces κ-intuitionistic fuzzy metric spaces, significantly broadening the scope of intuitionistic fuzzy metric spaces. This framework offers greater flexibility and applicability by incorporating multiple parameters (κ) into an intuitionistic fuzzy set. The study explores the properties of κ-intuitionistic fuzzy metric spaces, demonstrating that their topology is first-countable and that the corresponding metric space is Hausdorff. We establish a fixed-point theorem that generalizes and extends existing results for intuitionistic fuzzy metric spaces.